Calcium phosphate conversion technique: A versatile route to develop corrosion resistant hydroxyapatite coating over Mg/Mg alloys based implants - G.S. Hikku; C. Arthi; R.B. Jeen Robert; K. Jeyasubramanian; R. Murugesan (Journal of Magnesium and Alloys, 2022)
Globally, vast research interest is emerging towards the development of biodegradable orthopedic implants as it overcomes the toxicity exerted by non-degradable implants when fixed in the human body for a longer period. In this context, magnesium (Mg) plays a major role in the production of biodegradable implants owing to their characteristic degradation nature under the influence of body fluids. Also, Mg is one of the essential nutrients required to perform various metabolic activities by the human cells, and therefore, the degraded Mg products will be readily absorbed by the nearby tissues. Nevertheless, the higher corrosion rate in the biological environment is the primary downside of using Mg implants that liberate H2 gas resulting in the formation of cavities. Further, in certain cases, Mg undergoes complete degradation before the healing of damaged bone tissue and cannot serve the purpose of providing mechanical support. So, many studies have been focused on the development of different strategies to improve the corrosion-resistant behavior of Mg according to the requirement. In this regard, the present review focused on the limitations of using pure Mg and Mg alloys for the fabrication of medical implants and how the calcium phosphate conversion coating alters the corrosive tendency through the formation of hydroxyapatite protective films for enhanced performance in medical implant applications.